Accenting Lipid Peroxidation 2021
DOI: 10.5772/intechopen.95802
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation

Abstract: Lipid peroxidation (LPO) is initiated by the attack of free radicals (eg OH ·, O2- and H2O2) on cellular or organelle membranes phospholipids or polyunsaturated fatty acids (PUFA), and with the formation of various types of aldehydes, ketones, alkanes, carboxylic acids and polymerization products. It is an autoxidation process that results. These products are highly reactive with other cellular components and serve as biological markers of LPO. Malondialdehyde (MDA), a toxic aldehyde end product of LPO, causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…In cells, Fe 3+ produced by the Fenton reaction can be reduced back to Fe 2+ by the oxidation of O 2 ●− to O 2, originating a catalytic cycle [ 32 ]. The formed hydroxyl radical is a highly reactive oxidant (half-life of 10 −9 s) extracting hydrogen atoms from lipid molecules, starting lipid peroxidation [ 33 ]. The process of lipid peroxidation involves three main steps: initiation, propagation, and termination ( Figure 2 ).…”
Section: Iron-catalyzed Lipid Peroxidation In Cellsmentioning
confidence: 99%
“…In cells, Fe 3+ produced by the Fenton reaction can be reduced back to Fe 2+ by the oxidation of O 2 ●− to O 2, originating a catalytic cycle [ 32 ]. The formed hydroxyl radical is a highly reactive oxidant (half-life of 10 −9 s) extracting hydrogen atoms from lipid molecules, starting lipid peroxidation [ 33 ]. The process of lipid peroxidation involves three main steps: initiation, propagation, and termination ( Figure 2 ).…”
Section: Iron-catalyzed Lipid Peroxidation In Cellsmentioning
confidence: 99%
“…It is believed that oxidative stress results from an unbalanced population of prooxidant and antioxidant species (Yaman and Ayhanci, 2021). Total antioxidant capacity (TAC) is a commonly used analyte to determine the antioxidant status of biological materials and can determine how well the body fights against free radicals produced by a particular disease (Rubio et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Oils lose quality when malondialdehyde builds up in them during storage. This compound is responsible for the oxidation that leads to bad flavors and a rotten smell [40]. Many studies indicated the effect of fortifying different vegetable oils with different materials on the properties of theobarbituric acid.…”
Section: The Effect Of Reinforcement With Different Materials On Theo...mentioning
confidence: 99%